2021
DOI: 10.31557/apjcp.2021.22.7.2199
|View full text |Cite
|
Sign up to set email alerts
|

Use of E-Cigarettes and Associated Factors among Youth in Thailand

Abstract: Electronic cigarettes (e-cigarettes) were first marketed in China in 2004, then became available in Europe in 2006 and the US in 2007 (Henningfield and Zaatari, 2010;Riker et al., 2012). In less than ten years since e-cigarettes were introduced, e-cigarettes have become the most commonly used tobacco product among youths in many countries (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
40
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 50 publications
(56 reference statements)
6
40
2
Order By: Relevance
“…Most e-cigarette users in Thailand use them along with conventional cigarettes (dual usage) rather than using e-cigarettes to completely replace conventional cigarettes 12,25 . Some Thai users of e-cigarettes lack knowledge and understanding about the products they use 2 . This study found that the majority of adolescents in this sample were not current users of e-cigarettes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most e-cigarette users in Thailand use them along with conventional cigarettes (dual usage) rather than using e-cigarettes to completely replace conventional cigarettes 12,25 . Some Thai users of e-cigarettes lack knowledge and understanding about the products they use 2 . This study found that the majority of adolescents in this sample were not current users of e-cigarettes.…”
Section: Discussionmentioning
confidence: 99%
“…A 2015 national survey of e-cigarette use among Thai middle school students found that 3.3% (4.7% of boys and 1.9% of girls) were current (past 30-day) users 1 . The overall prevalence of e-cigarette use in 2019 among students in grades 7–12 was 3.7% (5.9% for male, and 1.3% for female students); among youth aged 14–16 years, the prevalence of e-cigarette use was 6.4% 2 . There has been a significant increase in e-cigarette use among US youth since 2011 3 .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Research in Thailand found that current smoking, use of e-cigarettes by parents, peer use of e-cigarettes, peer consent to smoking, and did not know the risk of smoking e-cigarettes were significantly associated with current e-cigarette use (30). Male gender, poor academic achievement, and poor life assets were significantly associated with e-cigarette use (30).…”
Section: Discussionmentioning
confidence: 99%
“…More recent articles published in Thailand about e-cigarettes use, for instance, a cross-sectional self-reported survey conducted in 2019 amongst 6167 adolescents aged 14–17 years in Bangkok, Thailand, found that adolescents had been using e-cigarettes in the last 30 days (6.7%) [ 7 ]. Similarly, a study conducted about e-cigarettes use amongst youth in Thailand showed that 7.2% had ever used e-cigarettes and 3.7% were current e-cigarettes users [ 8 ]. However, these recent articles about Thai e-cigarettes users were about adolescents.…”
Section: Introductionmentioning
confidence: 99%